Crosslinked copolymer with low dielectric constant and dissipation factor based on poly(2, 6‐Dimethylphenol‐co−2, 6‐Diphenylphenol) and a crosslinker. Issue 19 (1st July 2016) - Yang, Min Chi; Higashihara, Tomoya; Su, Hung Wen; Ueda, Mitsuru; Chen, Wen‐Chang
ABSTRACT: The crosslinked poly(2, 6‐dimethylphenol (95 mol %)‐ co −2, 6‐diphenylphenol (5 mol %)) (poly(2, 6‐DMP95 ‐ co −2, 6‐DPP5 )) was successfully developed as an insulating material separating conducting elements with a low dielectric constant and dissipation factor. The crosslinked poly(2, 6‐DMP95 ‐ co −2, 6‐DPP5 ) was prepared by the oxidative coupling polymerization of 2, 6‐DMP with 2, 6‐DPP, followed by the reaction with 4, 4′‐methylenebis[2, 6‐ bis (methoxymethyl)]phenol (MBMP) as a crosslinking agent. The crosslinked poly(2, 6‐DMP95 ‐ co −2, 6‐DPP5 ) exhibited a good thermal stability and glass transition temperature. The dielectric constant and dissipation factor of the crosslinked poly(2, 6‐DMP95 ‐ co −2, 6‐DPP5 ) were 2.6 and 0.004 at 10 GHz, respectively. Moreover, a flexible double layer copper clad laminate based on the crosslinked poly(2, 6‐DMP95 ‐ co −2, 6‐DPP5 ) composite was successfully prepared, indicating a useful material for high‐speed and high‐frequency electrical applications. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 3218–3223 Abstract : The crosslinked poly[2, 6‐dimethylphenol (95 mol %)‐ co −2, 6‐diphenylphenol (5 mol %)] [poly(2, 6‐DMP95 ‐ co −2, 6‐DDP5 )] was successfully developed as an insulating material for high‐speed and high‐frequency electrical applications.